Study of the features of hydrochemical characteristics and development of zooplankton in the area of water-air curtain type fish protection structure in the cooling reservoir of the SDPP - M. L. Kalaida; A. R. Saetov; M. F. Khamitova (Известия высших учебных заведений: Проблемы энергетики)
PURPOSE. Study of the features of hydrobiological characteristics of zooplankton development under operating conditions of a fish protection structure similar to a water-air curtain (WAC) at an energy facility.METHODS. Hydrobiological material was collected, processed and analyzed on the physical and chemical characteristics of water and on the qualitative and quantitative composition of zooplankton in the water intake area of the Zainskaya State District Power Plant. A comparative analysis of our own research and literature data on the characteristics of water in the area of a water-air curtain fish protection structure was carried out. The material was processed using generally accepted hydrobiological methods in the laboratory of the Department of Aquatic Bioresources and Aquaculture of Kazan State Energy University.RESULTS. It is shown that a fish protection device of the water-air curtain type is a multifunctional technical solution, which during operation changes the physical and chemical characteristics of the state of the ecosystem, especially in the bottom layer. It was revealed that a fish protection structure (FPS) like a water-air curtain does not reduce the species diversity of zooplankton. In the area where the WAC operates, the maximum abundance and biomass of zooplankton were noted compared to control stations. The basis of the number and biomass of zooplankton were crustaceans: cladocerans accounted for 50.2% of the total biomass, copepods accounted for 46.1%.CONCLUSION. Observations of the state of the ecosystem in the area of operation of the water-air curtain and assessment of water quality based on hydrobiological indicators revealed high water quality in the area where the WAC operates, and an improvement in the environmental situation.